2023
DOI: 10.3390/cells12060875
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Stimulation Increases the Secretion of Cardioprotective Extracellular Vesicles from Cardiac Mesenchymal Stem Cells

Abstract: Clinical trials have shown that electric stimulation (ELSM) using either cardiac resynchronization therapy (CRT) or cardiac contractility modulation (CCM) approaches is an effective treatment for patients with moderate to severe heart failure, but the mechanisms are incompletely understood. Extracellular vesicles (EV) produced by cardiac mesenchymal stem cells (C-MSC) have been reported to be cardioprotective through cell-to-cell communication. In this study, we investigated the effects of ELSM stimulation on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 70 publications
0
13
0
Order By: Relevance
“… 94 Zhang et al demonstrated that electrical stimulation method significantly increased the release of cardiac MSC-derived EVs, and the EVs obtained through a neutral sphingomyelinase 2 (nSMase2)-dependent mechanism had an enhanced cardioprotective effect in C-MSCs. 95 , 96 Our group has also developed a cellular nanoporation (CNP) technology 33 as shown in Figure 4 . In this work, cells were stimulated by transient electrical pulses to generate nanopores on the cell membrane, which in turn facilitated the loading of pDNA from the buffer into the cells.…”
Section: Generation Isolation and Purification Of Evsmentioning
confidence: 99%
“… 94 Zhang et al demonstrated that electrical stimulation method significantly increased the release of cardiac MSC-derived EVs, and the EVs obtained through a neutral sphingomyelinase 2 (nSMase2)-dependent mechanism had an enhanced cardioprotective effect in C-MSCs. 95 , 96 Our group has also developed a cellular nanoporation (CNP) technology 33 as shown in Figure 4 . In this work, cells were stimulated by transient electrical pulses to generate nanopores on the cell membrane, which in turn facilitated the loading of pDNA from the buffer into the cells.…”
Section: Generation Isolation and Purification Of Evsmentioning
confidence: 99%
“…As a result, Hu et al highlighted the direct correlation between an upregulation in Ca 2+ ion concentration and the increased secretion of EVs [ 288 , 291 ]. Similarly, Zhang et al exposed cardiac-MSCs (C-MSCs) to low-level ES from 2 to 72 h. There was a significant increase in the nSMase2 protein levels, crucial to EV biogenesis and release [ 292 ]. Compared to C-MSCs (control), C-MSCs (ES) produced a 38% increase in EV particles/mL concentration and diameter [ 292 ].…”
Section: Neurotrophic Support In Neuropathy Treatmentmentioning
confidence: 99%
“…Similarly, Zhang et al exposed cardiac-MSCs (C-MSCs) to low-level ES from 2 to 72 h. There was a significant increase in the nSMase2 protein levels, crucial to EV biogenesis and release [ 292 ]. Compared to C-MSCs (control), C-MSCs (ES) produced a 38% increase in EV particles/mL concentration and diameter [ 292 ]. Alternatively, with high voltage and exposure time, the hyperactive rate of nerve action potential proved to be damaging to the cell [ 291 ].…”
Section: Neurotrophic Support In Neuropathy Treatmentmentioning
confidence: 99%
See 2 more Smart Citations